Evolution of weak waves and central expansion waves in a non-ideal relaxing gas - Randheer Singh; J. Jena (Ain Shams Engineering Journal, 2016)
The main features of small amplitude waves generated by a planar piston-like surface in a planar flow of a vibrationally non-ideal relaxing gas are investigated. It is found that the analytical solution of the flow field for weak waves and central expansion wave propagation is influenced by the relaxation time and van der Waals excluded volume.